Critical Issues in Dental and Medical Management of Obstructive Sleep Apnea. (January 2020) - Lavigne, G.J.; Herrero Babiloni, A.; Beetz, G.; Dal Fabbro, C.; Sutherland, K.; Huynh, N.; Cistulli, P.A.
This critical review focuses on obstructive sleep apnea (OSA) and its management from a dental medicine perspective. OSA is characterized by ≥10-s cessation of breathing (apnea) or reduction in airflow (hypopnea) ≥5 times per hour with a drop in oxygen and/or rise in carbon dioxide. It can be associated with sleepiness and fatigue, impaired mood and cognition, cardiometabolic complications, and risk for transportation and work accidents. Although sleep apnea is diagnosed by a sleep physician, its management is interdisciplinary. The dentist's role includes 1) screening patients for OSA risk factors (e.g., retrognathia, high arched palate, enlarged tonsils or tongue, enlarged tori, high Mallampati score, poor sleep, supine sleep position, obesity, hypertension, morning headache or orofacial pain, bruxism); 2) referring to an appropriate health professional as indicated; and 3) providing oral appliance therapy followed by regular dental and sleep medical follow-up. In addition to the device features and provider expertise, anatomic, behavioral, demographic, and neurophysiologic characteristics can influence oral appliance effectiveness in managing OSA. Therefore, OSA treatment should be tailored to each patient individually. This review highlights some of the putative action mechanisms related to oral appliance effectiveness and proposes future research directions.